2018
DOI: 10.1515/med-2018-0012
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of retinopathy of prematurity with bronchopulmonary dysplasia

Abstract: AbstractRetinopathy of prematurity (ROP) and bronchopulmonary dysplasia (BPD) are diseases that occur only in preterm infants. The etiology of these disorders is multifactorial; however, it is believed that some of the factors in children presenting with BPD affect both the initiation and severity of ROP. The aim of the study was to evaluate the degree of clinical severity of ROP in infants with BPD compared to those without BPD. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 39 publications
5
16
0
Order By: Relevance
“…Holmström et al showed that BPD precedes ROP and acts as a risk factor for its development and severity [20]. Other authors support this theory since premature infants with BPD require oxygen therapy, which may increase the incidence of ROP [2124]. These results are consistent with other researches confirming that long-term mechanical ventilation and/or CPAP are risk factors for the development of severe forms of ROP [15, 25, 26].…”
Section: Discussionsupporting
confidence: 66%
“…Holmström et al showed that BPD precedes ROP and acts as a risk factor for its development and severity [20]. Other authors support this theory since premature infants with BPD require oxygen therapy, which may increase the incidence of ROP [2124]. These results are consistent with other researches confirming that long-term mechanical ventilation and/or CPAP are risk factors for the development of severe forms of ROP [15, 25, 26].…”
Section: Discussionsupporting
confidence: 66%
“…[56,57] Moreover, infants with intrauterine infection after birth always have a worse respiratory condition, which is typically treated with a higher concentration of oxygen and more advanced mechanical ventilation (such as invasive mechanical ventilation), which also increases the likelihood of ROP occurrence. [58,59] On the contrary, we found that the association of fungal sepsis with ROP was stronger than that of bacterial sepsis. In terms of the etiology of fungal sepsis, of the 7 studies included, 5 studies involved Candida sepsis.…”
Section: Discussionmentioning
confidence: 67%
“…NRDS is mainly characterized by respiratory failure and progressive dyspnea shortly after birth (16). The occurrence of RDS is mainly related to the long-term injury of respiratory epithelial cells and insufficient secretion of surfactant in alveolar epithelium.…”
Section: Discussionmentioning
confidence: 99%